Varactor‐incorporated bandpass filter with reconfigurable frequency and bandwidth. Issue 8 (August 2017) - Kumar, Amarjit; Pathak, Nagendra Prasad
Abstract: We report a varactor‐loaded tunable microstrip bandpass filter (BPF) with reconfigurable center frequency and bandwidth. The effects of loading varactors at intercoupled stepped‐impedance resonator (SIR) resonator and at tapped input/output port coupled‐lines are studied. Tuning elements are properly loaded at the middle of the coupled‐line sections for achieving tunable center frequency and bandwidth performance. Initial BPF (without loading varactors) is based on a half‐wavelength (λg /2–) coupled stepped‐impedance resonator (CSIR) structure. For the validation of the proposed concept, a hardware prototype is fabricated and characterized. A total of three varactors are used as the tuning elements. Only two dc control voltages are used for tuning the center frequency and bandwidth.